Ceramic properties of kaolinitic clay with monoaluminum phosphate (Al(H₂PO₄)₃) addition - Mocciaro, Anabella (2021)
The effect of monoaluminum phosphate (Al(H₂PO₄)₃) addition in the thermochemical process of a kaolinitic clay was studied and compared with the pure clay. Monoaluminum phosphate incorporation is of technological interest for the widely use of this material as an effective binder. From this point of view is important to clarify the processing strategy of kaolinitic clay-MAP based ceramics. This work comprised the characteristics of the obtained ceramics using differential thermal analysis, thermogravimetric analysis (TG), dilatometric analysis, X-ray powder diffraction with Rietveld refinement, mechanical resistance and textural properties. The addition of MAP did not affect the temperature of the kaolinite dehydroxilation (600–500 °C) but reduced this transformation as it was observed in TG curve. The amount of mullite decreased and cristobalite formation was stimulated with MAP presence in the samples fired at 1400 °C. Mullite cell parameters were not modified. The present study gives information for further clay-based materials designed with MAP. It can be concluded that the incorporation of low percentages of MAP in the potential formulation of technological ceramics would not imply important changes in the macroscopic properties of these type of ceramic materials.